Antecendents of culinary art career choice among vocational high school students: A case of TRNC - Özbaşar, Kurtuluş (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: The aim of this study is to investigate the high school graduating students’ culinary art intentions by testing the effects of personality traits, socio – cultural background and culinary art intention on culinary art choice. Many high school graduating students have difficulties in finding and choosing the right career to enter. However no research has focused on the factors that influence students in choosing tourism and tourism – related departments in TRNC. Therefore, this study aims to be a first and contribute to existing literature on other fields by investigating the relationship between personal traits, socio-cultural background, culinary art intention and culinary art choice of final year high school students in vocational schools in North Cyprus. A total of 270 questionnaires were distributed to the students who were in their final year studying in vocational schools. Out of the 270 questionnaires, 215 were collected. The sampling technique used for this study was judgmental sampling. This study has revealed that personality traits, socio – cultural background and culinary art intention all have a significant and positive relationship with culinary art career choice. Furthermore, limitations and directions for future research are presented at the end of the thesis. Keywords: Personality Traits, Socio-Cultural Background, Intention, Culinary Arts, North Cyprus. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu araştırmanın amacı, kişisel özelliğin, sosyokültürel yapının ve mutfak sanatları niyetinin mutfak sanatları seçiminin üzerindeki etkisini araştırarak lise son sınıf öğrencilerinin mutfak sanatları seçimini incelemektir. Bir çok mezun olacak olan lise son sınıf öğrencileri gelecekteki meslek seçimlerinde zorluk ve kararsızlık yaşamaktadır. Fakat, KKTC’deki bu öğrencilerin, turizm veya turizm ile ilgili meslek seçimini etkileyen faktörler ile ilgili bir çalışma olmadığından, bu araştırma, KKTC meslekokullarındaki lise son sınıf öğrencilerinin kişisel özelliğini, sosyokültürel yapısını ve mutfak sanatları niyetlerinin mutfak sanatları seçimlerinin üzerindeki etkisini araştırarak bir ilk olup varolan diğer mesleklerle ilgili olan literatüre katkıda bulunmayı amaçlamaktadır. KKTC meslekokullarındaki lise son sınıf öğrencilerine toplamda 270 anket dağıtılmıştır, Dağıtılan 270 anketten 215 anket geri alınmıştır. Olasılıksız yargısal örnekleme tekniğini kullanarak örneklem seçilmiştir. Araştırmanın sonucuna göre kişisel özelliğin, sosyokültürel yapının, mutfak sanatları niyetinin ve mutfak sanatları seçiminin arasında olumlu bir ilişkinin olduğu saptanmıştır. Buna ek olarak yöneticiler için öneriler yapılmış, tezin sınırlılıkları açıklanmış ve gelecekteki araştırmalar için öneriler sunulmuştur. Anahtar Kelimeler: Kişisel Özellik, Sosyokültürel Yapı, Niyet, Mutfak Sanatları, Kuzey Kıbrıs.
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2014. Supervisor: Prof. Dr. Hüseyin Araslı.
Keywords: Tourism; Culinary Art, Tourism - High School Students; Personality Traits, Socio-Cultural Background, Intention, Culinary Arts, North Cyprus